Sastra Menjadi Cambuk Perjuangan Rakyat Palestina dalam Cerpen-cerpen Karya Ummu Kauṡar Kajian Adab Al-Muqāwamah: Kajian Adab Al-Muqāwamah - Kamala, Ananda Emiel (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
Abstract Ummu Kauṡar is one of the many Palestinian writers whose work is a condition to be called resistance literature to Israel, so that it raises the question of the symbols of resistance and what fighting spirit is there in its short stories? The purpose of this research is to uncover the Palestinian-Israeli conflict so that it raises the adab al-muqāwamah which is one of the ways to fight the invaders and to know the symbols and the spirit of the struggle of the Palestinian people in Ummu Kauṡar's short story. The theory that is used is the theory of adab al-muqāwamah namely the results of the thoughts poured into literary works and used as a means of resistance and a spirit of the struggle for a nation to stop the oppression and colonization that occurred in order to preserve the nation and homeland from the hands of the invaders. The results of this study indicate that the symbols of resistance and the spirit of struggle used by Ummu Kauṡar in his short stories have led to a portrait of the lives of Palestinian women and children as well as the conditions of the homeland and the Palestinian nation. His work can also be a whip of the spirit of struggle for the Palestinian people against Israel to reclaim their homeland rights. Key Words: Resistance, Palestine, Israel, Adab al-Muqāwamah